Очерки по истории и культуре староверов Эстонии III [Studies on the history and culture of Old Believers in Estonia III] - Кюльмоя [Külmoja], И. П. [Irina] (Acta Slavica Estonica, 2012)
Acta Slavica Estonica is an international series of publications on current issues of Russian and other Slavic languages, literatures and cultures. This volume continues the tradition of publishing studies on the history and culture of the Old Believers in Estonia. It includes research papers on the topic, as well as transcripts of recorded texts from the Old Believers. The special focus of the volume is on the island Piirissaar, its history, architecture, people and their language, customs and traditions.